Assessing the effects of lipid extraction and lipid correction on stable isotope values (δ13C and δ15N) of blubber and skin from southern hemisphere humpback whales. (29th June 2021) - Groß, Jasmin; Fry, Brian; Burford, Michele A.; Bengtson Nash, Susan
Abstract : Rationale: The coupled analysis of δ 13 C and δ 15 N stable isotope values of blubber and skin biopsy samples is widely used to study the diet of free‐ranging cetaceans. Differences in the lipid content of these tissues can affect isotopic variability because lipids are depleted in 13 C, reducing the bulk tissue 13 C/ 12 C. This variability in carbon isotope values can be accounted for either by chemically extracting lipids from the tissue or by using mathematical lipid normalisation models. Methods: This study examines (a) the effects of chemical lipid extraction on δ 13 C and δ 15 N values in blubber and skin of southern hemisphere humpback whales, (b) whether chemical lipid extraction is more favourable than mathematical lipid correction and (c) which of the two tissues is more appropriate for dietary studies. Strategic comparisons were made between chemical lipid extraction and mathematical lipid correction and between blubber and skin tissue δ 13 C and δ 15 N values, as well as C:N ratios. Six existing mathematical normalisation models were tested for their efficacy in estimating lipid‐free δ 13 C for skin. Results: Both δ 13 C and δ 15 N values of lipid‐extracted skin (δ 13 C: −25.57‰, δ 15 N: 6.83‰) were significantly higher than those of bulk skin (δ 13 C: −26.97‰, δ 15 N: 6.15‰). Five of the six tested lipid normalisation models had small error terms for predicting lipid‐free δ 13 C values. The average C:N ratio of lipid‐extracted skin was within the lipid‐free range reported in other studies, whereas the average C:N ratio of blubber was higher than previously reported. Conclusions: These results highlight the need to account for lipids when analysing δ 13 C and δ 15 N values from the same sample. For optimised dietary assessments using parallel isotope analysis from a single sample, we recommend the use of unextracted skin tissue. δ 15 N values should be obtained from unextracted skin, whereas δ 13 C values may be adequately lipid corrected by a mathematical correction.